2018
DOI: 10.21276/ijcmr.2018.5.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hematological and Biochemical Profile of Early Dengue Patients

Abstract: Introduction: Dengue infection has been identified as the fastest spreading mosquito-borne viral disease by World Health Organization. This study is an attempt to elucidate the positive laboratory profile of serologically diagnosed early dengue patients so as to facilitate early diagnosis, treatment and management. Material and methods: A total of 100 cases diagnosed as dengue based on rapid immunological card tests (NS1 antigen and Ig M antibodies) were analyzed for haematological and biochemical parameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
2
7
1
Order By: Relevance
“…Thrombocytopenia impacts management raising concerns about transfusions, their effects and hospitalisation 1,7,8,10,16 . Our study showed a predominance of dengue in young age and males in accordance with few studies 5,12,16 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thrombocytopenia impacts management raising concerns about transfusions, their effects and hospitalisation 1,7,8,10,16 . Our study showed a predominance of dengue in young age and males in accordance with few studies 5,12,16 .…”
Section: Discussionsupporting
confidence: 93%
“…8,24 Leucopenia noted in 38% in accordance with few, 15 varied in other 16,18 being associated with mild than severe thrombocytopenia in support of few studies claming association with dengue fever than severe dengue. 23 We had 62% cases of lymphocytosis with equal distribution in mild and severe thrombocytopenia in accordance with few studies, suggesting it was a consistent feature in the course of dengue, 4,12 other differed. 25 Significant atypical lymphocytosis, noted in 52%, had highest association with severe than mild thrombocytopenias and was in accordance with few studies indicating it to be a marker and severity prognosticator for dengue.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Lymphocytosis is characteristic of acute symptomatic DENV infection; however, typically, leukopenia, neutropenia, and increased hematocrit are observed [41]. Little is known about hematological parameters following inapparent DENV infection, although leukocytosis with neutrophilia has been seen early in DENV infection [42]. In 1952, Sabin described a mild type of DENV with fever lasting from 24 to 36 h with no rash or leukocytosis [43].…”
Section: Discussionmentioning
confidence: 99%
“…Dengue infection has been identified as the fastest spreading mosquito-borne viral disease by World Health Organization [1]. It is an important febrile illness with wide spectrum of manifestations seen mainly in tropical countries [2].…”
Section: Introductionmentioning
confidence: 99%